Design, synthesis and screening of indole acetic acid-based tri-azo moieties as antioxidants, anti-microbial and cytotoxic agents - Javaid, Maryam; Haq, Ihsan-Ul; Nadeem, Humaira; Fatima, Humaira; Khan, Arif-Ullah; Irshad, Nadeem (Frontiers in Pharmacology, 2023)
Multidrug resistance and infectious disease have enormous spread despite drug discovery and development advancements. 1,2,4 -triazoles have been extensively studied, playing an imperative role in many pathologic conditions. A series of Schiff base triazoles; derived from Indole -3- acetic acid with substituted Benzaldehydes(5a-5g) were designed, synthesized, and evaluated through various Spectroanalytical techniques. SwissADME was used to assess physicochemical properties and pharmacokinetic drug-likeliness behavior. (5a-5g) were evaluated for their varied biological potential through antioxidant, antimicrobial, enzyme inhibition, and cytotoxic evaluation. Schiff bases express drug-like nature as they follow Lipinski’s rule of five. 5b showed good antioxidant potential in total antioxidant capacity (TAC) & total reducing power (TRP) assays and was most active in the library in % free radical scavenging assay (%FRSA), showing 32% inhibition at 50 μg/mL concentration. Compounds showed antibacterial activity against various tested strains. 5e & 5f showed a minimum inhibitory concentration (MIC) value of 3.12 μg/mL for P.aeruginosa and K.pneumoniae, respectively. In the antifungal assay, only 5e inhibited one strain with a zone of inhibition >6mm. These synthetic molecules possess good cytotoxic potential in the Brine Shrimp Lethality screening; 5c,5d, and 5f exhibited LC50 =5.7 μg/mL. In the protein kinase inhibition assay, 5a, 5b, and 5g demonstrated inhibitory potential, showcasing the zone of inhibition as 7.5-10.5mm for the bald one and 6-7.5 for the clear zone. These findings suggest that the compounds have antibacterial & cytotoxic potential, and there is a chance for further research and development in this area.